Fascists in exile - Persian, Jayne, author.
1 online resource.
Keywords: "Fascists in Exile tells the extraordinary story of the war criminals, collaborators and fascist ultranationalists who were resettled in Australia by the International Refugee Organisation between 1947 and 1952. It explores the far-right backgrounds and continuing political activism of these displaced persons in Australia, adding to our knowledge of the development of Australian anti-communism in the 1950s. These individuals argued that they had been caught between National Socialism and Soviet communism. What might that have meant for their migration and resettlement trajectories? Beyond 'Nazi-hunting', what can this tell us about the challenge they posed to international and national forms, both in Europe and in Australia? This book demonstrates that fascist ideation could not only survive the war's end but that it continued to be transnational and transcultural. At the same time, anti-fascist protests and then the war crimes investigations of the late 1980s exposed problematic pasts, a legacy with which Australia is still reckoning. The text will appeal to those with an interest in the far right, Australian migration and refugee issues"--